Web Mobile Based on E- Marketing at Jumiran Stores using the Customer Relationship Management (CRM) Method - Tri Ragil Saputra; Rian saputra; Elmayati; Lukman Sunardi; Shely yunanda sari; Yurina putri lestari; Agung sanjaya (ADPEBI, 2022)
Jumiran Business's market share is now limited to the neighborhood around the store because sales are still conducted manually or customers come directly to the store.Product data storage for the delivery of information is still done manually utilizing a ledger as a medium for product data recording, resulting in messy and undetailed data storage.The goal of implementing the CRM approach in e-commerce or e-marketing is to simplify the marketing, sales, and support processes for business owners, making it simpler for customers to access product information at Jumiran Stores.The following are the outcomes of the study on the sales system using the CRM method: main page, product page, and customer